Cho hàm số g( x ) = x^2 - 5x + 6/| x - 2|. Tìm lim x đến 2^ + g( x ) và lim x đến 2^ - g( x ).
Cho hàm số g(x)=x2−5x+6|x−2|.
Tìm lim và \mathop {\lim }\limits_{x \to {2^ - }} g\left( x \right).
Cho hàm số g(x)=x2−5x+6|x−2|.
Tìm lim và \mathop {\lim }\limits_{x \to {2^ - }} g\left( x \right).
Lời giải:
Ta có: g\left( x \right) = \frac{{{x^2} - 5x + 6}}{{\left| {x - 2} \right|}} = \frac{{\left( {x - 2} \right)\left( {x - 3} \right)}}{{\left| {x - 2} \right|}} = \left\{ \begin{array}{l}\frac{{\left( {x - 2} \right)\left( {x - 3} \right)}}{{x - 2}}\,\,\,n\^e 'u\,\,x - 2\,\, > 0\\\frac{{\left( {x - 2} \right)\left( {x - 3} \right)}}{{ - \left( {x - 2} \right)}}\,\,\,n\^e 'u\,\,x - 2 < 0\end{array} \right.
= \left\{ \begin{array}{l}x - 3\,\,\,n\^e 'u\,\,x\,\, > 2\\3 - x\,\,\,n\^e 'u\,\,x < 2\end{array} \right..
Do đó, \mathop {\lim }\limits_{x \to {2^ + }} g\left( x \right) = \mathop {\lim }\limits_{x \to {2^ + }} \left( {x - 3} \right) = 2 - 3 = - 1;
\mathop {\lim }\limits_{x \to {2^ - }} g\left( x \right) = \mathop {\lim }\limits_{x \to {2^ - }} \left( {3 - x} \right) = 3 - 2 = 1.